Allergies in Phlebology: A National Survey and Review of Literature - Visch, Birgitte M.; de Roos, Kees-Peter (Phlebologie, 2022)
Background Type I and type IV hypersensitivity can play an important role in phlebology with potential severe consequences for patients and treatment results.Methods A review of literature was performed for allergic reactions in patients treated for venous insufficiency and venous leg ulcers (VLU), together with a study in the Dutch and European centre for adverse drug reactions. Besides, we performed a survey among 37 Dutch medical hospitals to investigate the incidence of treatment allergies.Results Hypersensitivity reaction is seen in 46–76% of patient with VLU; about 20% of these reactions are caused by wound dressings products. In 11 centres urticarial and respiratory complaints were seen and 3 systemic allergic reactions in phlebological treatments. In Europe 25 cases of systemic reactions were reported.Conclusion Patients with VLU with slow healing tendency should undergo allergy tests. Type I hypersensitivity with anaphylactic reaction, also to sclerosing fluid or tumescent, is very rare.
Keywords: Allergie; Überempfindlichkeit; Varikosis; Ulcus cruris venosum; Polidocanol